Pengaruh Profitabilitas, Kebijakan Utang, Kebijakan Dividen dan Ukuran Perusahaan terhadap Nilai Perusahaan - Agus Bandang; Weney Kanatya Mangopo; Rahmawati H.S; Haerial Haerial; Mahfiza Mahfiza (Al-Buhuts, 2026)
Increasing competition in the food and beverage industry is driving companies to optimize the factors that influence firm value; however, empirical findings regarding the role of profitability, debt policy, dividend policy, and firm size still show inconsistent results. This study aims to analyze the effects of profitability, debt policy, dividend policy, and firm size on firm value in companies in the food and beverage subsector listed on the Indonesia Stock Exchange during the 2022–2024 period. The study employs a quantitative approach using secondary data obtained from companies’ financial statements. The research sample was determined using purposive sampling and consisted of 20 companies with a total of 60 observations. The data were analyzed using multiple linear regression with the aid of SPSS software. The results indicate that profitability (β = 1.305; p < 0.001), dividend policy (β = 0.383; p = 0.012), and firm size (β = 0.879; p < 0.001) have a positive and significant effect on firm value, whereas debt policy (β = –0.065; p = 0.537) does not show a significant effect. Profitability is the variable with the most dominant influence on firm value. Furthermore, the research model explains 59.8% of the variation in firm value, while the remainder is influenced by other factors outside the research model. These findings indicate that investors in the food and beverage subsector tend to place greater emphasis on a firm’s ability to generate profits, distribute dividends, and manage its business scale compared to its level of debt utilization when evaluating firms. Therefore, companies need to prioritize strategies to improve profitability and implement financial policies aimed at increasing firm value. These findings also reinforce the role of financial performance indicators and firm characteristics in determining firm value and provide implications for management and investors in formulating financial strategies to enhance firm value